Separation of Enantiomers and CD Spectra of Au40(SCH2CH2Ph)24: Spectroscopic Evidence for Intrinsic Chirality - Knoppe, Stefan; Dolamic, Igor; Dass, Amala; Bürgi, Thomas (Angewandte Chemie International Edition, 2012)
Chirality unveiled: Thiolate‐protected Au40(SR)24 clusters were enantioenriched using an HPLC approach. CD spectra show strong mirror‐image responses, indicating the intrinsic chirality of a cluster of unknown structure protected with achiral ligands.